Effect of NaCl on Growth, Ion Accumulation and Oxidative Enzymes of Suaeda nudiflora Moq. - T. Balasubramanian1,2, P. Amuthavalli1,; P. Sivaraman1, S. Sivasankaramoorthy1, T. (Recent Research in Science and Technology, 2011)
The effect of different concentration of NaCl (0-750 mM) salinity on growth, ion accumulation and enzyme activities were studied in a halophytic species of Suaeda nudiflora. The upper limit for the survival of this species at 750 mM NaCl and the optimum level for the better growth was 400 mM NaCl. Beyond, these concentrations the growth rate sharply declined Na+ and Cl- ions increased with increasing salinity upto the extreme level of NaCl, on the other hand K+ content decreasing with increasing salinity. The Ca2+ content and Na+/K+ ratio increased steadily with salinity. The accumulation of cat ions was greater in leaves then in stem and root. NaCl treatment stimulated the activities of ATPase upto the extreme salinity level. However, catalase, peroxidase and polyphenol oxidase activities increased upto the optimal level and at higher concentrations showed decreasing trend. The changes of enzyme activities and their possible role in salt tolerance of Suaeda nudiflora have been studied.